Myofibroblasts are distinguished from activated skin fibroblasts by the expression of AOC3 and other associated markers - Hsia, L; Ashley, N; Ouaret, D; Wang, L; Wilding, J; Bodmer, W (National Academy of Sciences, 2016)
Pericryptal myofibroblasts in the colon and rectum play an important role in regulating the normal colorectal stem cell niche and facilitating tumor progression. Myofibroblasts previously have been distinguished from normal fibroblasts mostly by the expression of α smooth muscle actin (αSMA). We now have identified AOC3 (amine oxidase, copper containing 3), a surface monoamine oxidase, as a new marker of myofibroblasts by showing that it is the target protein of the myofibroblast-reacting mAb PR2D3. The normal and tumor tissue distribution and the cell line reactivity of AOC3 match that expected for myofibroblasts. We have shown that the surface expression of AOC3 is sensitive to digestion by trypsin and collagenase and that anti-AOC3 antibodies can be used for FACS sorting of myofibroblasts obtained by nonenzymatic procedures. Whole-genome microarray mRNA-expression profiles of myofibroblasts and skin fibroblasts revealed four additional genes that are significantly differentially expressed in these two cell types: NKX2-3 and LRRC17 in myofibroblasts and SHOX2 and TBX5 in skin fibroblasts. TGFβ substantially down-regulated AOC3 expression in myofibroblasts but in skin fibroblasts it dramatically increased the expression of αSMA. A knockdown of NKX2-3 in myofibroblasts caused a decrease of myofibroblast-related gene expression and increased expression of the fibroblast-associated gene SHOX2, suggesting that NKX2-3 is a key mediator for maintaining myofibroblast characteristics. Our results show that colorectal myofibroblasts, as defined by the expression of AOC3, NKX2-3, and other markers, are a distinctly different cell type from TGFβ-activated fibroblasts.